Dampak Struktur Kepemilikan, Financial Leverage, Board Director terhadap Nilai Perusahaan - Ambarwati, Sri Dwi Ari; Astuti, Rini Dwi (Jurnal Keuangan dan Perbankan, 2015)
This study tried to analyze the effect of ownership structure, financial leverage, size of board directors and sales Growth on the performance of companies with lower growth opportunities , whether there is a proxy growth opportunities with low PER. This research was conducted at the manufacturing company with the selection criteria for purposive sampling method 2010-2012 period, based on the criteriaÂ  the obtained sample of 32companiesÂ  withÂ  low growth opportunities. Thus obtained 96 obervasi for each group. The results showed that: 1). simultaneously the ownership structure, financial leverage, size of board directors and sales Growth affect the performance ofÂ  companies with low growth opportunities. 2). Partially, it was found empirical evidence that financial leverage and variable size of board directors significantly affect the companyâs performance with lower growth opportunities. For institutional ownership structure revealed a significant effect on performance, but at a rate of 10% alpha tolerated.